Association between serum levels of bioavailable vitamin D and negative symptoms in first-episode psychosis. (30th September 2016) - Yee, Jie Yin; See, Yuen Mei; Abdul Rashid, Nur Amirah; Neelamekam, Sasi; Lee, Jimmy
Abstract: Total vitamin D levels had been commonly reported to be lowered in patients with chronic psychotic illnesses in countries from the higher latitudes. However, studies on patients with first episode psychosis (FEP) are limited. In this study we investigated serum concentrations of total and bioavailable vitamin D levels in FEP patients compared to healthy controls and the association between symptom severity and vitamin D components. A total of 31 FEP patients and 31 healthy controls were recruited from Institute of Mental Health, Singapore. FEP patients were identified using Structured Clinical Interview for DSM-IV Axis I disorders (SCID-1) and severity symptoms were assessed using the positive and negative syndrome scale (PANSS). Sera from participants were analyzed for total vitamin D, vitamin D-binding protein (DBP) and bioavailable vitamin D. Linear regressions were performed to examine the associations between serum total and bioavailable vitamin D and the PANSS subscales. Current study noted a significantly lower bioavailable vitamin D was in the FEP group and an association between bioavailable vitamin D and negative symptoms in FEP patients in a population with a consistent supply of sun exposure throughout the year. Highlights: Compare vitamin D levels in first psychotic patients and healthy controls. Evaluate association between vitamin D and severity symptoms. Bioavailable vitamin D level was statistically lower in patients than controls. A higher negative symptom was associated with lower bioavailable vitamin D levels.